Perceptions of Global Citizen by Rover Scouts and Leadership Scouts - Wangdi, Sonam; Tenzin, Karma (International Journal of Language, Literature and Culture, 2021)
The purpose of the survey study was to examine the perception of Global Citizen by: (1) Rover, who had undergone 21 days of Scouts Leadership Training, (2) Rover, who has not undergone 21 days of Scouts Leadership Training, (3) Nazhoen Scouts who have undergone 21 days of Scouts Leadership Training, and (4) to examine whether the perceptions of Global Citizen are determined by the number of years in the Scouting. The questionnaires were administered using google form to (n=209) (Male=87, Female=122, (1) =90, (2) =74, (3) =45 (4) = (0-5 Years=48, 5-10 Years=91 ,10-15 Years=70).Reysen and Katzarska-Miller (2013) Global Citizen Scale questionnaire within the total Cronbach’s alpha reliability coefficient of (α=.92) and nine subscales viz Normative Environment(0.86), Global Awareness(0.74), Global Citizenship Identification(0.81), Intergroup Empathy(0.65), Valuing Diversity(0.79), Social Justice(0.81), Environmental Sustainability(0.79), Intergroup helping(0.80), and Responsibility to Act(0.83) were used to examine the perceptions of Global Citizen. The results of the survey study revealed that out of the nine subscales of the Global Citizen Scale of Reysen and Katzarska-Miller (2013), Normative Environment, Global awareness, Global Citizenship Identification, and Intergroup Empathy have been perceived as Somewhat Agree (5.00-5.99): Valuing Diversity, Social Justice, Environmental Sustainability, Intergroup Helping, and Responsibility to Act have been perceived as Agree (6.00-6.99). The overall perception on the Global Citizen is established at x ̅=6.09 and σ=0.90. The correlation and regression line between the number of years being in the Scouting indicated very strong and positive associations between the